A Combine Effect of Firm Characteristics and Corporate Social Responsibility on Supply Chain Performance - Mohd Saudi, Mohd Haizam; Wijaya, Aida; Arwaty, Dini; Zaman, Dr. Fazluz; Purnamasari, Dyah (ExcelingTech, 2019)
Objective of this study is to examine the role of firm characteristics in supply chain performance (SCP) with mediating role of corporate social responsibility (CSR). Various lower income countries are facing different issues in supply chain which has effect on SCP. These issues are related to the firm characteristics. Firm characteristics include; size and ownership. Additionally, this study examined the mediation effect of CSR between firm characteristics and SCP. 500 questionnaires were distributed to get the response of supply chain employees in Indonesian supply chain companies. The companies only dealing with supply chain were selected to get response. The companies which were involved in other activities are not included in the survey. After data collection, data were examined through structural equation modeling. It is found that firm characteristics have direct relationship with CSR and CSR has direct relationship with SCP. Moreover, CSR playing a mediating role between firm characteristics and SCP.